Risk of unexpected uterine leiomyosarcoma during laparoscopic procedures: Experience from a single tertiary institute in Italy. Issue 2 (5th May 2021) - Surace, Alessandra; Baù, Maria Grazia; Privitera, Sebastiana; Botta, Giovanni; Danese, Saverio; Plazzotta, Claudio; Mitidieri, Marco; Picardo, Elisa
Abstract: Objective: To evaluate the incidence of occult uterine sarcomas and investigate whether an accurate and well‐established preoperative assessment for uterine fibroids could help identify uterine sarcomas more effectively. Methods: A retrospective analysis of patients who underwent gynecological laparoscopic surgery for presumed uterine fibroids at Sant'Anna Hospital, a single tertiary institute in Turin, Italy, between January 2003 and December 2019. Results: Over the 17‐year period, 5826 laparoscopic surgical procedures (myomectomies or subtotal/total hysterectomies) were performed for presumed uterine fibroids. A total of 48 patients with a final diagnosis of uterine sarcoma were identified, the majority of which ( n  = 39; 81.3%) were recognized as suspicious uterine sarcomas during the preoperative assessment, and morcellement was avoided. The occurrence of unexpected uterine sarcomas was 0.1% (6/5826). Morcellation was conducted in one patient with uterine sarcoma. Conclusion: Analysis of our data showed that unexpected uterine sarcomas are uncommon. Accurate preoperative evaluation can help avoid, but does not exclude, the possibility of morcellation of unknown uterine sarcomas. Abstract : Data analysis showed that unexpected uterine sarcomas are uncommon. Accurate preoperative evaluation can help avoid, but does not exclude, the possibility of morcellation of unknown uterine sarcomas.